PENGARUH EMPLOYER ATTRACTIVENESS DAN KOMPENSASI TERHADAP MINAT MELAMAR PEKERJAAN - Margaretha Noprisda Sinaga; Dismas Persada Dewangga Pramudita (LPPM STIE YKPN Yogyakarta, 2023)
Companies are currently competing to be superior so they can survive in an increasingly hypercompetitive market. High-quality human resources are an important factor that potentially support companies to become superior. A recruitment process that runs well will produce quality human resources. Effective recruitment can be carried out when recruitment sources can be filtered well. Therefore, this research aims to determine the influence of employer attractiveness and compensation on interest in applying for jobs. The respondents in this research were 50 Atma Jaya University Yogyakarta students, Class of 2019. Data collection in this research was carried out by distributing questionnaires online. The data that has been obtained is processed using multiple linear analysis techniques with the help of SPSS 29 software. The results of this research show that employer attractiveness and compensation have a positive and significant effect on interest in applying for jobs.